The Effect of the Game Method on Students' Motivation and Cognitive Ability - Ruth May; Dian Rachmawati; Evi Amelia (Universitas Sultan Ageng Tirtayasa, 2023)
This study aimed to the effect ofthe game method on motivation and cognitive capacities. The study employed a quasi-experimental approach with a randomized block design, with the game method as the independent variable and motivation and cognitive ability as the dependent variables. The research sample consisted of VIII C as the control class and VIII A as the experimental class. The sampling approach used was random sampling. A questionnaire was used to assess student motivation. A questionnaire was used to assess student motivation, a posttest was used to assess cognitive capacities, and an observation sheet was used to assess learning implementation. According to the findings, the average score of students' motivation in the experimental class was 61, placing them in the very high group. Students in the experimental class have a strong cognitive ability, scoring 72.36. The P value for the t-test was 0,05, showing that the gaming method influenced students' motivation and cognitive ability on human movement system concepts.